ANALISIS PERLAKUAN AKUNTANSI PENGAKUAN PENDAPATAN DAN BEBAN JASA KONSTRUKSI BERDASARKAN SAK ETAP PADA PT. KARYA SULAWESI UTARA - Tatuu, Maikel Ariel; Pantow, Andreuw Kristian; Korompis, Sintia Nurani; Kaparang, Revleen Mariana; Walukow, Ivoletti Merlina (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Revenue and expenses recognition in construction companies is a critical aspect in ensuring the fairness of the presented financial statement. In general, construction projects are long-term or span multiple accounting periods, depending on the construction contract. Therefore, revenue measurement should be based on the completion level of the construction work. This research was conducted at PT. Karya Sulawesi Utara using a qualitative approach and comparative descriptive data analysis technique. PT. Karya Sulawesi Utara recognizes revenue on cash basis, where revenue is recognized when cash is received, which is not in accordance with Indonesia Accounting Standard for Non-Publicly-Accountable Entities (SAK ETAP). However, PT. Karya Sulawesi Utara recognizes expenses in accordance with SAK ETAP. PT. Karya Sulawesi Utara is still applying an inappropriate method for revenue recognition. The company is recommended to use the percentage completion method.